A Java Environment for High-Performance Computing - Lobosco, Marcelo; Amorim, Claúdio; Loques, Orlando (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2001)
There has been an increasing research interest in extending the use of Java towards high-performance demanding systems such as scalable web servers, multimedia applications, and large-scale scientific applications. However, given the low performance provided by current Java implementations, these application domains pose new challenges to both the application designer and systems developer. In this paper we present CoJVM (Cooperative Java Virtual Machine), a new Java environment for high-performance computing designed to speed up Java applications when executing on DSM based architectures implemented on clusters of workstations. The shared memory implementation is based on the HLRC DSM protocol and takes advantage of run-time information, extracted from the NM, to improve application performance.